Unveiling the Giant: Understanding Large Vulvar Fibroepithelial Polyps: A Case Report with Review of Literature - Priyanka Malhotra; Manjaree Morgaonkar; Akash Ramakrishna Shetty; Vishwas Rahangdale (Nepal Journal of Dermatology, Venereology & Leprology)
Fibroepithelial stromal polyps (FEPs), commonly known as acrochordons, are benign lesions of mesenchymal origin, typically found in the vulvovaginal area. Their growth is believed to be hormone-sensitive, often stimulated by hormonal changes, pregnancy, or prolonged hormone use, and they mostly occur in women of reproductive age. We present a case involving a 47-year-old woman with a large, painless, pedunculated mass on the right labia majora that progressively grew over a year. The patient had difficulty walking and refrained from intercourse due to the mass. Despite a previous hysterectomy, a pelvic ultrasound revealed no significant changes. Physical examination showed a soft, non-tender, hyperpigmented mass without signs of inflammation or ulceration. A dermatologist diagnosed it as a fibroepithelial polyp, confirmed by histopathological examination after excision. Differential diagnoses include aggressive angiomyxoma, angiomyofibroblastoma, sarcoma, and other conditions, clinical and histopathologic features can differentiate. Complete surgical excision is the preferred treatment to prevent recurrence, with cryotherapy or cauterization as alternatives for smaller polyps. Long-term follow-up is essential to monitor for recurrence.